Perencanaan untuk Monitoring pada Skema â€œIzin Pemanfaatan Hutan Perhutanan Sosialâ€ di Kabupaten Tulungagung - Putri, Dicky Fernanda; Mindarti, Lely Indah; Shobaruddin, Muhammad (Jurnal Ilmiah Administrasi Publik, 2020)
The modern forestry industry has led to the dissociation of the communities surrounding forests and deforestation, resulting in the Community welfare gap and loss of forest land cover. In overcoming this, the government issued a new policy of social forestry with IPHPS scheme that aims to provide the opportunity to the community around the forest to legally manage the forest in the working area of Perum Perhutani. This research aims to determine the planning of monitoring on IPHPS scheme in Tulungagung district that can be used to encourage in improving and strengthening the plan. This research uses descriptive research methods with a qualitative approach. The results showed that stakeholders have not conducted any planning for monitoring so that, the author made monitoring planning based on the desired stakeholder results, fact field and monitoring planning UNDP (2009).